2016
DOI: 10.2134/agronj2015.0245
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yield and Nodulation Response to Crop History and Inoculation

Abstract: Soybean [Glycine max (L.) Merr.] inoculation was imposed on a long-term continuous grain sorghum [Sorghum bicolor (L.) Moench] and soybean cropping systems study with and without manure application at Mead, NE. Th e objective was to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…In Fehrow, the nodulation rate, leghemoglobin, content and shoot nitrogen concentration in soil with soybean history were similar for non-inoculated and inoculated soybean seeds, showing no response to the commercial inoculation (Figure 1). This finding is in consonance with several previous studies in France (Revellin et al, 1996;Obaton et al, 2002) and at 73 environments in the USA (De Bruin et al, 2010;Mason et al, 2016). It is, however, in contrast to a common perception that the nodulation rate and symbiotic performance improve by using the inoculants containing elite strains of Bradyrhizobia (Mendes et al, 2004;Argaw, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Fehrow, the nodulation rate, leghemoglobin, content and shoot nitrogen concentration in soil with soybean history were similar for non-inoculated and inoculated soybean seeds, showing no response to the commercial inoculation (Figure 1). This finding is in consonance with several previous studies in France (Revellin et al, 1996;Obaton et al, 2002) and at 73 environments in the USA (De Bruin et al, 2010;Mason et al, 2016). It is, however, in contrast to a common perception that the nodulation rate and symbiotic performance improve by using the inoculants containing elite strains of Bradyrhizobia (Mendes et al, 2004;Argaw, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…This isolate is capable of forming nodules with soybeans more effectively than the commercial isolates. Another possibility might be that the soil was contaminated by Bradyrhizobia through wind and/ or water erosion as well as through farming equipment used over the years (Larson, 2013;Mason et al, 2016). Vargas et al (1994), in Brazil, found a strain of B. japonicum in soil samples, although the sampled site was thousands of kilometers away from the area where it had been introduced as an inoculant.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there were differences between locations for overall yield, there were no differences among the inoculant treatments for seed yield. Seed yield findings corroborated previous studies where fields with a recent history of soybean throughout the Midwest (De Bruin et al, 2010;Mason et al, 2016) and mid-South (Golden et al, 2016) did not observe a yield increase from the added inoculant. Similarly, number of root nodules were not different among the treatments, which agrees with previous findings that rhizobia within the soil produces adequate nodulation for maximum yield (Caldwell and Vest, 1970).…”
supporting
confidence: 89%
“…We support this assertion with the enhanced nodulation, grain yield, total N uptake by grains, and PHI obtained with the commercial inoculants relative to the uninoculated control. Thus, previous history of rhizobia inoculation and soybean cultivation would have a positive effect on grain yield of the subsequent soybean crop, which contradicts the earlier works of Mason et al (2016) and Chowdhury et al (1983).…”
Section: Effects Of Previous Inoculation On Yield and Total N Uptakementioning
confidence: 75%